2013
DOI: 10.1155/2013/704532
|View full text |Cite
|
Sign up to set email alerts
|

Fournier's Gangrene Associated with Local Cutaneous HPV Lesions in a Previously Healthy Girl

Abstract: A case of an 11-year-old prepubertal girl with Fournier's gangrene is presented. The diagnosis was posed after the disease had progressed to the typical clinical picture of frank gangrene. A benign viral infection, common warts, possibly represents the initiating event of the development of this necrotizing soft tissue infection. The development of childhood Fournier's gangrene in association with viral infections has been reported in the past. An optimal outcome was achieved by aggressive antibiotic and surgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…Lu et al [ 12 ] also reported the case of an 8-month-old girl with Fournier gangrene caused by Escherichia coli , which was complicated by septic shock and septic associated encephalopathy[ 12 ]. The majority of pediatric cases of Fournier gangrene have been reported in previously healthy children, who may appear well in the early stages of the disease and thus escape diagnosis, as in our case[ 3 ].…”
Section: Discussionmentioning
confidence: 86%
“…Lu et al [ 12 ] also reported the case of an 8-month-old girl with Fournier gangrene caused by Escherichia coli , which was complicated by septic shock and septic associated encephalopathy[ 12 ]. The majority of pediatric cases of Fournier gangrene have been reported in previously healthy children, who may appear well in the early stages of the disease and thus escape diagnosis, as in our case[ 3 ].…”
Section: Discussionmentioning
confidence: 86%
“…A GF foi relatada também por Tsinti et al [15] por apresentar maior predisposição a pessoas com infecções virais, descrevendo as lesões por HPV um forte fator para o seu desenvolvimento. Outro fator predisponente relatado na literatura por Khemees et al [16], que considera a bactéria Neisseria meningitidis causadora da GF, ocasionando a uretrite que tem uma alta incidência em homens homossexuais devido a alterações no comportamento sexual.…”
Section: A Atuação Do Enfermeiro Na Prevenção Da Gangrena De Fournier Nos Homensunclassified